Fluoride and organic matter removal from groundwater using nanofiltration membrane - Noor Safiah, Sohame @ Suhaimi (2012)
High fluoride concentrations in groundwater, up to more than 30 mg/L,occur widely,in many parts of the world. Nanofiltration(NF)membrane performance on fluoride removal from high fluoride content water was investigated in this study.The aim of this work is,on the other hand,to observe the influence of some operational parameters on the defluoridation performance. Nanofiltration was selected in this research since it has the smallest porous size that exhibit good performance in separation process compare to ultrafiltration and microfiltration membrane.Nanofiltration was prepared by interfacial polymerization.Nanofiltration membrane were synthesized by reacting aqueous solution of triethanolamine and organic solution of trimesoyl chloride in hexane.Separation test was carried out by using single test by separating the fluoride and water using synthetic fluoride.Nanofiltration membranes successfully reducing fluoride with the acceptable levels.